What the Devil Speaks About: Rereading Michael Taussig’s The Devil and Commodity Fetishism in South America - Kroesbergen-Kamps, Johanneke (NTT, 2025)
Michael Taussig’s The Devil and Commodity Fetishism in South America (1980) has had a continuing impact as an inspiration for ethnographies of resistance and the material turn in anthropology. Perhaps the most enduring influence is its analysis of quasi-religious narratives as a critique of Western, hegemonic systems. The article traces Taussig’s text’s lasting impact on the ethnography of the devil and concludes, however, that one crucial problem in Taussig’s analysis remains to be solved.